(untitled) (University Journal of Zoology, Rajshahi University, 2009)
The genotypic variability and correlation coefficients were studied in thirty five hybrid populations for five egg characters. Variations among genotypes were highly significant (P < 0.001). Phenotypic coefficient of variation was higher than genotypic coefficient of variation for all the characters. Of them unfertilized and dead egg percentage showed highest difference between genotypic and phenotypic coefficient of variation suggesting most influence of environment on these characters. Majority of the characters showed high heritability except hatching percentage. Furthermore total number of egg laying per female showed high genetic advance together with high heritability, which indicates the importance of additive gene effect of this character. The genotypic correlations were higher than phenotypic correlation for majority of the characters under study except DEP Vs TEL and DEP Vs UEP. These low phenotypic correlations could be due to a modifying effect of environment and the association of characters at genotypic level. Hatching percentage, blue egg percentage and unfertilized egg percentage showed both positive and negative significant correlation to each other. Therefore, proper attention should be given to these characters specially total number of egg laid by female and hatching percentage in selection programme for genetic gain in Bombyx. mori. Key words: Genetic variability, correlation, B. mori. Â doi:10.3329/ujzru.v27i0.1946 Â Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 13-16